The effect of target cost in sustainability support - AL-Mashkoor, Imad A.S.; AL-Maliki, Hanan Raheem Leabi (Edelweiss Applied Science and Technology, 2024)
The research objective mainly to demonstrate the effect of apply technique the target costing in sustainability support, by costs reduction through the optimal use of resources, where the value chain analysis method was adopted to determine the value-adding activities in the company and distinguish them from non-value-adding activities and work to exclude or reduce those activities to make the cost equal to the target cost of competing and similar products, all of which works to sustainability support in terms of the environment, human resources and social capital, laboratory data was adopted to clarify the research problem and to achieve its objective and hypothesis by applying target cost technology for the purpose of the costs reduction of production oxidized asphalt and oil waste. - Among the most important conclusions reached by the research: The fact that companies follow the target cost method has a major role in achieving competitive advantage for the company’s products through studying the market and competitive products in competing companies in order to determine the target selling price for those products, as well as determining the target profit margin by the company’s administrative on the basis of that study, a comprehensive survey of similar companies, also this method has a major role sustainability achieves in several dimensions (environmental, social, and human), through this method, the cost reduction of production and thus the effect of this reduction in sustainability support, he researcher then reached a set of recommendations, the most important of which are: Companies must provide the appropriate conditions to continuously apply the target costing method in order to achieve competitive advantage and maintain their market position and status by gaining and fulfilling market desires, also this method must be used in order to achieve sustainability as a result of preserving the environment from the side effects caused by companies due to product damage or harmful releases, as well as enhancing public relations between companies and external parties, in addition to supporting human resources and ensuring their rights and safety at work.